Peningkatan Pengetahuan dan Keterampilan Penanganan Low Back Pain bagi Kader Kesehatan di Puskesmas Kecamatan Kendari Barat, Kota Kendari Sulawesi Tenggara Tahun 2025 [Enhancing Knowledge and Skills in Managing Low Back Pain for Health Fasililator at the Kendari Barat District Community Health Center, Kendari City, Southeast Sulawesi in 2025] - Satrio Wicaksono; Sufiah Asri Mulyawati; Ashaeryanto Ashaeryanto; Muhammad Rustam H Noertika; Mariana Asmaningdiah; Dewinta Nur Alvionita; Lindia Aksa; Izur Fisabilillah Aminuddin (Indonesia Berdaya, 2026)
Low back pain (LBP) is one of the most common musculoskeletal disorders worldwide, with a global prevalence of 60–80% among adults. This condition results in limitations of daily activities, decreased productivity, and reduced quality of life. In Indonesia, LBP is frequently reported among both productive and elderly age groups, with major risk factors including non-ergonomic working postures, insufficient physical activity, and degenerative processes. In Kendari Barat District, LBP cases are often encountered at community health centers , particularly among individuals with diverse occupations such as office workers, traders, and laborers. These jobs often involve repetitive physical activity or prolonged static postures, highlighting the need for stronger promotive and preventive interventions at the community level.The purpose of this community service program is to strengthen the capacity of health fasilitators in understanding, preventing, and managing LBP through education, ergonomic training, and stretching exercises. The methods applied include interactive counseling, practical simulations, and cadre mentoring at the Kendari Barat Community Health Center. A total of 60 health cadres participating in this activity are expected to contribute by providing education to the community in their respective environments.                                                              Abstrak. Low back pain (LBP) merupakan salah satu gangguan muskuloskeletal dengan prevalensi global tinggi, yaitu 60–80% pada orang dewasa, dan berdampak pada keterbatasan aktivitas, penurunan produktivitas, serta kualitas hidup. Di Indonesia, keluhan LBP banyak dijumpai pada kelompok usia produktif maupun lanjut usia, dengan faktor risiko utama berupa postur kerja tidak ergonomis, kurangnya aktivitas fisik, serta proses degeneratif. Di Kecamatan Kendari Barat, kasus LBP sering ditemukan di Puskesmas, terutama pada masyarakat dengan variasi pekerjaan seperti pegawai kantoran, pedagang, dan buruh. Kondisi ini menegaskan perlunya intervensi promotif dan preventif yang lebih kuat di tingkat komunitas. Tujuan dari program pengabdian masyarakat ini adalah meningkatkan kapasitas kader kesehatan dalam memahami, mencegah, dan menangani LBP secara sederhana melalui edukasi, pelatihan ergonomi, serta latihan peregangan. Metode yang digunakan meliputi penyuluhan interaktif, simulasi praktik, dan pendampingan kader di Puskesmas Kecamatan Kendari Barat. Sebanyak 60 kader kesehatan yang mengikuti kegiatan ini diharapkan mampu memberikan berkontribureka dalam memberikan edukasi kepada Masyarakat dilingkungan mereka masing-masing.